Effect of Environmental Conditions on Silicon solar cells (Journal of the College of Basic Education, 2023)
The aim of this work is to study the effect of dust on the performance and efficiency of solar cells . Two solar panels were used clean and dusty each consists of 12 solar cells.The remaining challenge is to find accost-effective way to apply these principles to construct a low-cost solar cell with high and stable efficiency.Photovoltaic (PV) cells have social and commercial value only when they are used in a system to provide a service. This research has given a brief overview of the technical and economic considerations that allow the cells to provide such a service.